Role of Return, Risk, and Correlation in Investment Decisions and Portfolio Selection - Rama Krishna, Y. (Indian Journal of Finance, 2010)
This study measures the Holding Period Return (HPR), Daily and Annualized Returns, Unsystematic Risk, and Correlation among stocks belongs to similar industry type of S&P CNX NIFTY stocks. S&P CNX 500 was considered as a market index. Daily closing price of stocks and closing value of market index were collected from National Stock Exchange (NSE) of India for a period between 31-12-2008 and 31-12-2009. During this period, the market has 244 trading days. The objectives of this study are to empirically assess the buy and hold strategy, market timing strategy, and role of correlation in portfolio selection. The holding period return was calculated for every three months considering the stock’s closing price as on 31st December 2008 as a base period. Daily average returns were calculated using the continuous compounding method. A correlation analysis was performed to understand the movement of stock related to market index. Cross order correlation was performed to know the relation of stocks belonging to same industry. Results of the study support the buy and hold strategy and forty seven percent of stocks outperformed the market index. A significant positive correlation was found among the stocks and market index. However, few stocks have very high correlation values and few have weak correlations.